Income-Related Inequalities in Health Service Utilisation in 19 OECD Countries, 2008-2009 - Devaux, Marion (OECD Publishing, 2012)
This Working Paper examines income-related inequalities in health care service utilisation in OECD countries. It extends a previous analysis (Van Doorslaer and Masseria, 2004) to 2008-2009 for 13 countries, and adds new results for 6 countries, for doctor and dentist visits, and cancer screening. Quintile distributions and concentration indices were used to assess inequalities. For doctor visits, horizontal equity was assessed, i.e. the extent to which adults in equal need of physician care appear to have equal rates of utilisation. The paper considers the evolution of inequalities over time by comparing results with the previous study, as data permit. Health system financing arrangements are examined to see how these might affect inequalities in health service use
Keywords: Social Issues/Migration/Health